Seasonal variations of volatile constituents of Hemizygia bracteosa (Benth.) Briq. aerial parts from Benin - KPOVIESSI, Dossou Sika Salomé; AGBANI, Pierre O.; GBAGUIDI, FERNAND; GBENOU, Joachim; SINSIN, AUGUSTIN BRICE; ACCROMBESSI, COFFI GEORGES; Bero, Joanne; MOUDACHIROU, MANSOUROU; Quetin-Leclercq, Joëlle (My University, 2016)
Essential oils from fresh aerial parts of Hemizygia bracteosa (Benth.) Briq. were extracted by steam distillation. The oil yield from plants collected during the hot season (February) and during the cold season (August) were 0.12 ± 0.01% and 0.25 ± 0.02%, respectively. GC/FID and GC/MS analyses allowed us to identify a total of 65 compounds, representing 97% of the hydrodistillate. The main components of the oil from the hot period were (E)-b-farnesene (64 ± 0.04%), b-elemene (7.4 ± 0.05%), trans-nerolidol (6.2 ± 0.04%), and a-muurolene (2.7 ± 0.03%). The essential oil from the cold season was characterized by the presence, as major compounds, of (E)-b-farnesene (67 ± 0.04%) along with b-caryophyllene (3.6 ± 0.06%), b-elemene (3.3 ± 0.05%), 7-epi-a-selinene (3.1 ± 0.01%) and p-cymene (2.5 ± 0.04%). This is the first report of these components in the essential oil of Hemizygia bracteosa (Benth.) Briq.
Keywords: Hemizygia bracteosa; Lamiacea; Essential oil composition; Seasonal variations; (E)-b-Farnesene; b-Elemene.